ANALISI FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia) - Nihayatul Farikhah, 16.05.62.0040; Kartika, Andi (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the factors that influence audit delay in the property and real estate sub-sector companies listed on the “Bursa Efek Indonesia” for the period of 2014-2017. In this study the method used in sampling is the purposive sampling method. The type of data used is secondary data. The research data was analyzed with descriptive statistics and the method of data analysis using multiple linear regression with F test and t test. The results of the study are partial (t test), the results show that company size, KAP size, has a significant positive effect on audit delay. While solvency, profitability, and audit opinion have a significant negative effect on audit delay. And for audit committee variables there is no significant negative effect on audit delay.